SWOT Analysis of Off-pump Coronary Artery Bypass Grafting - Zafar, Amna; Raja, Shahzad G. (British Journal of Healthcare and Medical Research, 2026)
Off‑pump coronary artery bypass grafting (OPCAB) has undergone significant evolution since its introduction as an alternative to conventional on‑pump CABG. By avoiding cardiopulmonary bypass (CPB) and minimizing aortic manipulation, OPCAB aims to reduce perioperative morbidity, neurological complications, and systemic inflammatory responses. Despite these theoretical advantages, its adoption has varied widely across institutions due to concerns regarding graft patency, completeness of revascularization, and operator dependency. This state‑of‑the‑art review provides a comprehensive SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis of OPCAB, integrating evidence from randomized trials, meta‑analyses, and large observational studies. The strengths of OPCAB include reduced stroke risk, lower perioperative morbidity in high‑risk populations, decreased bleeding and transfusion requirements, and compatibility with anaortic total arterial revascularization. Weaknesses include technical complexity, variability in surgeon experience, concerns regarding long‑term graft patency, and inconsistent evidence from randomized trials. Emerging opportunities include the expansion of anaortic no‑touch techniques, integration with minimally invasive and robotic platforms, advances in intraoperative imaging, and the potential for subspecialty training to standardize outcomes. Threats include declining surgeon experience, competition from percutaneous coronary intervention and hybrid revascularization strategies, persistent skepticism regarding patency and completeness of revascularization, and economic or technological barriers to widespread adoption. Through a structured SWOT framework, this review synthesizes contemporary evidence to clarify OPCAB’s current role and future trajectory in coronary surgery. The analysis highlights the importance of surgeon expertise, institutional commitment, and technological integration in optimizing outcomes. OPCAB remains a valuable strategy for selected patients, particularly those at elevated risk for neurological complications or adverse effects of CPB.